2022
DOI: 10.3389/fimmu.2022.811551
|View full text |Cite
|
Sign up to set email alerts
|

Response of Human Liver Tissue to Innate Immune Stimuli

Abstract: Precision-cut human liver slice cultures (PCLS) have become an important alternative immunological platform in preclinical testing. To further evaluate the capacity of PCLS, we investigated the innate immune response to TLR3 agonist (poly-I:C) and TLR4 agonist (LPS) using normal and diseased liver tissue. Pathological liver tissue was obtained from patients with active chronic HCV infection, and patients with former chronic HCV infection cured by recent Direct-Acting Antiviral (DAA) drug therapy. We found that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(90 reference statements)
0
0
0
Order By: Relevance
“…They found that this resulted in long-term viability under standard cell culture conditions. This approach has since been employed in several other studies 9 , 27 , 49 . Enabling the use of standard culture conditions improves the practicality of the PCLS model given the ubiquity of cell culture incubators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that this resulted in long-term viability under standard cell culture conditions. This approach has since been employed in several other studies 9 , 27 , 49 . Enabling the use of standard culture conditions improves the practicality of the PCLS model given the ubiquity of cell culture incubators.…”
Section: Discussionmentioning
confidence: 99%
“…For a more clinically relevant model, PCLS can be collected from patient biopsies or from animal models after liver fibrosis or cirrhosis is induced in vivo. A variety of fibrosis etiologies have been investigated with this approach, including alcohol 26 , hepatitis infection 27 , non-alcoholic steatohepatitis (NASH) 26 , 28 , cholestasis 29 33 , and chemical hepatotoxins 26 , 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…For a more clinically relevant model, PCLS can be collected from patient biopsies or from animal models after liver fibrosis or cirrhosis is induced in vivo. A variety of fibrosis etiologies have been investigated with this approach, including alcohol 26 , hepatitis infection 27 , non-alcoholic steatohepatitis (NASH) 26,28 , cholestasis [29][30][31][32][33] , and chemical hepatotoxins 26,34,35 .…”
Section: Introductionmentioning
confidence: 99%